Hadoop backup and recovery solutions : learn the best strategies for data recovery from Hadoop backup clusters and troubleshoot problems /: learn the best strategies for data recovery from Hadoop backup clusters and troubleshoot problems. (2015) - Barot, Gaurav; Patel, Amij; Mehta, Chintan
No abstract available